Dzieje odnalezienia drzewa Krzyża Świętego. Ustalenia i wątpliwości historyczne - Wróblewski, Paweł (Analecta Cracoviensia, 2008)
At the end of the last century modern scholarly debate concerning the legend of finding the True Cross started again. S. Heid, S. Borgehammar i J. W. Drijvers presented different reconstructions of beginnings of Inventio crucis. Heid maintained that the Holy Wood was not found, Borgehammar wrote that this event really had place and that Helena discovered the lignum crucis. Drijvers argues with Borgehammar about finding the trophy but he thinks that He- lena did not participate in that event. Recently in polish publications about relics and True Cross the Borgehammar’s thesis was accepted without any analysis of the ancient texts and without discussion about the state of research.In this paper author investigates the Greek, Latin (and translations of Syriac) texts, evaluates the veracity of the legend and comments all thesis, which have been already published. A literary analysis shows that Helena was not connected with the discovery of the Holy Wood, she was not in Jerusalem at the time the Christ’s tomb was found and the construction of the Church of Holy Sepulchre started - only in this time the lignum crucis may have been discovered. Building work in Jerusalem started before she went on her pilgrimage to Palestine. Inventio Crucis was evidently later construct.Moreover there is no proof that the discovery indeed had place. The earliest sources do not mention it and we know nothing about place where Cross may have been found. On the other hand it is also possible that some chunks of wood were discovered during the buildings work in Jerusalem, and later (rather not immediately) these pieces were claimed to be the fragments of the True Cross. Lignum crucis was undoubtedly venerated in the end of the fourth century in the Church of the Holy Sepulchre. The legend could explained the presence of the relics of the Cross (which soon became a favourite goal of pilgrimage) foremost in Jerusalem and gave a reason for presence of fractions of the trophy in other places. It is also probable that Cyril of Jerusalem initiated writing the story and used it for his own purposes.We cannot definitely determine that "finding" of the Cross was a real event or not but we can prove that Helena did not discover the Holy Wood.